The Quality of E-Government Management, Information Security and Quality - Aferdita Qekaj-Thaçi; Ledri Thaçi (Emerging Science Journal, 2023)
The purpose of the presented paper was to present the state of e-government services in the Republic of Kosovo within the management of electronic services and the role of ICT in data security and quality. E-government is an important sphere in Kosovo, which has been shown to have positively influenced the provision of services to all stakeholders, taking care of the security and quality of these services. This paper belongs to the qualitative and quantitative types, where a total of 115 subjects, experts, and users of e-government services participated and gave their opinions against these services. A literature review was used to process qualitative data, while a questionnaire was used to process quantitative data with experts and users of e-government services. From the results of the research, we understood that the level of use of e-government services in the Republic of Kosovo is high and that there is a high level of data security and quality of services, where the role of ICT in the management of e-data-government is essential and very important. It is recommended that, according to the results of this study, direct access to the management of these services should be considered and offered to ensure the sustainability of e-government services in the Republic of Kosovo. Doi: 10.28991/ESJ-2023-07-01-016 Full Text: PDF